Severity of rolling reconstituted high-moisture barley on ensiling characteristics and in vitro ruminal fermentation - Beverly A. Lynch; Gabriel O. Ribeiro; Timothy Mutsvangwa; Gregory B. Penner (Journal of Dairy Science)
ABSTRACT: Barley grain sources with variable kernel sizes makes adequate and consistent processing of kernels challenging. This study evaluated how the severity of processing for reconstituted high-moisture (65% on DM basis) barley (RHB) affects ensiling characteristics and in vitro ruminal fermentation. Three independent sources of light (<630 g/500 mL) and heavy (>670 g/500 mL) barley were blended to create 4 sources of variable kernel sized barley (646 g/500 mL). Reconstituted high-moisture barley rolled using a 1.40-mm gap width for finely processed RHB (RHBF), a 1.86-mm gap width for medium processed RHB (RHBM), or a 2.31-mm gap width for coarsely processed RHB (RHBC) was ensiled for 1 or 5 mo with dry rolled barley (DRB; roller gap width 1.86 mm) used as a control. The 1-mo RHB and the DRB were further evaluated using the rumen in vitro simulation technique (RUSITEC) to investigate the effects of severity of processing for RHB on ruminal fermentation, and gas, methane, and microbial protein production. Using a randomized complete block design (n = 4), 16 fermenters from 2 RUSITEC apparatuses were used to assess the 4 sources and 4 processing treatments. The addition of water increased kernel width before rolling and resulted in increased kernel length, width, and thickness for RHB relative to DRB. Increasing processing severity for RHB linearly increased kernel width. The percentage of fine particles (<1.18 mm) was greater for DRB than RHBF, but did not differ by processing severity for RHB. Dry matter, OM, and starch disappearance were not different between DRB and RHBF, but linearly increased with increasing processing severity for RHB. Fermenter pH tended to be less for DRB relative to RHBF. In conclusion, the reduction in fine particles with the addition of water for RHB may prevent a decline in fermenter pH and when processed to achieve the same processing index using a smaller roller gap width, yielded similar DM and OM disappearance suggesting a lesser risk for low ruminal pH without compromising digestibility.